Amino- and carboxy-terminal deletion mutants of Gs alpha are localized to the particulate fraction of transfected COS cells (The Rockefeller University Press, 1992)
To elucidate the structural basis for membrane attachment of the alpha subunit of the stimulatory G protein (Gs alpha), mutant Gs alpha cDNAs with deletions of amino acid residues in the amino and/or carboxy termini were transiently expressed in COS-7 cells. The particulate and soluble fractions prepared from these cells were analyzed by immunoblot using peptide specific antibodies to monitor distribution of the expressed proteins. Transfection of mutant forms of Gs alpha with either 26 amino terminal residues deleted (delta 3-28) or with 59 amino terminal residues deleted (delta 1-59) resulted in immunoreactive proteins which localized primarily to the particulate fraction. Similarly, mutants with 10 (delta 385-394), 32 (delta 353-384), or 42 (delta 353-394) amino acid residues deleted from the carboxy terminus also localized to the particulate fraction, as did a mutant form of Gs alpha lacking amino acid residues at both the amino and carboxy termini (delta 3-28)/(delta 353-384). Mutant and wild type forms of Gs alpha demonstrated a similar degree of tightness in their binding to membranes as demonstrated by treatment with 2.5 M NaCl or 6 M urea, but some mutant forms were relatively resistant compared with wild type Gs alpha to solubilization by 15 mM NaOH or 1% sodium cholate. We conclude that: (a) deletion of significant portions of the amino and/or carboxyl terminus of Gs alpha is still compatible with protein expression; (b) deletion of these regions is insufficient to cause cytosolic localization of the expressed protein. The basis of Gs alpha membrane targeting remains to be elucidated.